A química na literatura de Primo Levi: o capítulo Cério e a energia dos alimentos medida por um calorímetro - Freitas, Patrícia Lenise de [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Bibliographic reviews point to the lack of exploration of the integration of literature with the sciences. The importance of this work is related to the integration of literature in chemistry teaching in an interdisciplinary way, making the student realize that science is neither fragmented nor linear. The teaching-learning process is a continuous construction and there are several influences that determine this path. Thus, it is reported in this paper the articulation between chemistry and literature through the Cerium chapter of the book The Periodic Table by Primo Levi, which promotes discussions about the energy released by food that can be measured by a calorimeter. We also discuss an experience developed in an elective discipline applied in a full time school in the city of Matão - SP, together with undergraduate students of Chemistry at UNESP Araraquara. The focus of this work is on chemistry teaching from the literature of Primo Levi, who was a jewish chemist who survived the Holocaust in Nazi Germany. Here we will report how a teaching activity was developed in the area of thermodynamics, to work specifically on the concept of heat, involving the energy of food using a home calorimeter. The excerpt from the book used for information gathering was the chapters of Cerium, in which the author describes his search for food in a chemistry lab. We discuss about Primo Levi’s work and life, the chemical concepts evolved in a calorimeter and how they were developed in a high school context.

Revisões bibliográficas apontam a falta de exploração da integração da literatura com as ciências. A importância deste trabalho está relacionada à integração da literatura no ensino de química de forma interdisciplinar, fazendo com que o aluno possa perceber que a ciência não é fragmentada e nem linear. O processo de ensino-aprendizagem é uma construção continua e há várias influências que determinam esse caminho. Dessa forma é relatado, neste trabalho, a articulação entre química e literatura por meio do capítulo “Cério”, do livro A Tabela Periódica de Primo Levi, que fomenta discussões sobre a energia liberada pelos alimentos que pode ser medida por um calorímetro. Discutimos também uma experiência desenvolvida em uma disciplina eletiva aplicada em uma escola estadual do Programa de Ensino Integral na cidade de Matão – SP, em conjunto com alunos de Licenciatura em Química da UNESP de Araraquara. O foco deste trabalho é voltado para a área do ensino de química a partir da literatura do Primo Levi, o qual foi um químico e escritor judeu sobrevivente do Holocausto na Alemanha Nazista. Relataremos como foi desenvolvida uma atividade de ensino na área de termodinâmica, para trabalhar especificamente o conceito de calor, envolvendo a energia dos alimentos com a utilização de um calorímetro caseiro. O trecho do livro usado para a coleta das informações foi o capítulo “Cério”, no qual o autor descreve sua busca por alimentos em um laboratório de química. Discutimos sobre a vida e obra de Primo Levi, os conceitos químicos envolvidos no calorímetro e como eles foram desenvolvidos em um contexto de nível médio.
Chemistry in Primo Levi's literature: the Cerium chapter and the energy of food measured by a calorimeter
Keywords: Primo Levi; Ensino de ciências; Calorímetro